PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN DAN DAMPAKNYA TERHADAP LOYALITAS PELANGGAN - M. Khulwan Madih, 09.05.51.0015 (Students Journal of Economic and Management, 2013)
This study is intended to analyz the effect of service quality on customer satisfaction and its impact on customer loyalty, as well as to test the mediation between service quality on customer loyalty with customer satisfaction as mediator variables were tested using path analysis (path analysis). The object of this research is E- Cinema at E- Plaza Semarang. Determination of the sample using purposive accidental sampling method. Respondents in this study were 100 respondents. this study, the data processing using the application SPSS (Statistical Package for Social Sciences). The method of data analysis using the validity and reliability. Further analysis using multiple linear regression research and testing mediation to explain the relationship between variables. The result is service quality and satisfaction have positive and significant effect on loyalty. This shows if the service quality and satisfaction better will increase loyalty. While the services quality from test mediation indirect effect on loyalty, so the service quality affects loyalty through customer satisfaction.Keywords: Service Quality, Customer Satisfaction, Customer Loyalty